Towards transparent disclosure : theoretical review - Sulku, Anniina (2015)
There exists less trust towards organizations in the field of government and business. This means that organizations have strong need to find better ways to reinforce their transparent disclosure. Transparency can be defined as making information available whereas disclosure meeting the expectations of stakeholders. When the public experiences organizational disclo- sure dialogic and true, it improves the relationships organization has with its public and result as trust, support and satisfaction among the public. In the literature, concepts transparency and disclosure have many definitions and di- mensions. This means it is difficult to define the relationship between transparency and disclo- sure. Hence, the research problem of this study is: how transparency and disclosure are port- rayed together. Research questions of this study are 1) from which perspectives are transpa- rency and disclosure discussed in the literature on organizations, communication and society, 2) what kinds of relationships do the concepts of transparency and disclosure have and 3) which concept, transparency or disclosure, better meets organizational needs?